Portugal : Eleventh Review Under the Extended Arrangement, and Request for Extension of the Arrangement and Waivers of Applicability of End-March Performance Criteria. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Eleventh Review Under the Extended Arrangement and Request for Extension of the Arrangement focuses on Portugal's macroeconomic framework and fiscal policy. Sovereign bond yields have declined sharply, buoyed by the improved economic outlook and increased investor appetite for higher yielding southern European debt. The recent upturn in domestic demand remains susceptible to changes in market sentiment and any renewed policy uncertainty. The operational performance of state-owned enterprises continues to improve, while the privatization program advances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet